2013
DOI: 10.1093/humrep/det129
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian-specific Tex19.1 gene plays an essential role in spermatogenesis and placenta-supported development

Abstract: This work was supported by the Centre National de la Recherche Scientifique (CNRS), the Institut National de la Santé et de la Recherche Médicale (INSERM) (Grant Avenir), the Ministère de l'Education Nationale, de l'Enseignement Supérieur et de la Recherche, the Université de Strasbourg, the Association Française contre les Myopathies (AFM) and the Fondation pour la Recherche Médicale (FRM) and Hôpitaux Universitaires de Strasbourg.The authors have nothing to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 31 publications
4
54
3
Order By: Relevance
“…1E). Conversely, after 2 h of maturation, the mRNA coding for Tex19.1, a suppressor of transposon activation (Ollinger et al, 2008;Reichmann et al, 2013;Tarabay et al, 2013), became progressively associated with ribosomes up to the MII stage (Fig. 1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E). Conversely, after 2 h of maturation, the mRNA coding for Tex19.1, a suppressor of transposon activation (Ollinger et al, 2008;Reichmann et al, 2013;Tarabay et al, 2013), became progressively associated with ribosomes up to the MII stage (Fig. 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Both ribosome loading and protein expression show that TEX19.1 progressively accumulates during meiotic progression, with a maximum reached in MII. Tex19.1-null mice have been generated, but the inactivation of this gene in females either produces no phenotype (Tarabay et al, 2013) or decreased fecundity (Ollinger et al, 2008), suggesting that oocyte maturation is not prevented or only marginally affected when Tex19.1 is ablated. Conversely, TEX19.1 plays an essential role during male spermatogenesis as Tex19.1-null males are infertile owing to spermatogenic arrest at meiosis between pachytene and metaphase of MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5C). A literature search revealed that homozygous knockouts for Spint1 (Tanaka et al, 2005), Plac1 (Jackman et al, 2012), Tex19.1 (Tarabay et al, 2013), Kcnk1 (Millar et al, 2006), Tfap2a (Schorle et al, 1996;Zhang et al, 1996) and Prom2 (Tang et al, 2010) had been phenotypically characterized previously, with three, namely Spint1, Plac1 and Tex19.1, displaying a placenta phenotype. Whereas Plac1 −/− and Tex19.1 −/− mice exhibit milder placenta defects that manifest in late pregnancy (Jackman et al, 2012;Tarabay et al, 2013), Spint1 −/− mice have been reported to display an early placenta defect with lethality at E10.5 (Tanaka et al, 2005;Fan et al, 2007;Szabo et al, 2007), similar to the phenotype we found in Grhl2 −/− mice.…”
Section: Identification Of Placental Grhl2 Target Genes By Integratedmentioning
confidence: 99%
“…Conversely, TEX19.1 plays an essential role during male spermatogenesis as Tex19.1-null males are infertile owing to spermatogenic arrest at meiosis between pachytene and metaphase of MI. It has also been found that Line 1 and intracisternal A-particle (IAP) transposon levels are increased in the Tex19.1-null mice (Ollinger et al, 2008, Tarabay et al, 2013. Spermatogenesis is very sensitive to the activation of endogenous retroviruses, as documented by several knockout models, whereas transposon activation has less of an effect on mammalian oogenesis.…”
Section: Discussionmentioning
confidence: 99%